Fatty Acid Metabolism and Idiopathic Pulmonary Fibrosis - Geng, Jing; Liu, Yuan; Dai, Huaping; Wang, Chen (Frontiers in Physiology, 2022)
Fatty acid metabolism, including the de novo synthesis, uptake, oxidation and derivation of fatty acids, plays several important roles at cellular and organ levels. Recent studies have identified characteristic changes in fatty acid metabolism in idiopathic pulmonary fibrosis (IPF) lungs, which implicates its dysregulation in the pathogenesis of this disorder. Here, we review the evidence for how fatty acid metabolism contributes to the development of pulmonary fibrosis, focusing on the profibrotic processes associated with specific types of lung cells, including epithelial cells, macrophages, and fibroblasts. We also summarize the potential therapeutics that target this metabolic pathway in treating IPF.